Litogeochemistry and mineral chemistry from Correas massif rocks - Da Mata, Suelen Portughesi [UNESP]; Godoy, Antonio Misson [UNESP]; Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Luvizotto, George Luiz [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
The Correas Massif is located in the southern region of São Paulo state, related to the neoproterozoic granitogenesis evolution in the northern part of Apiaí Terrain and intrusive in the surrounding rocks of the Água Clara Formation metavolcanicsedimentary sequence, from Açungui Supergroup and in Três Córregos Granitic Complex rocks. It constitutes an elongated granite stock of 5 km2 in the ENE-WSW direction and presents associated mineralizations of cassiterite and wolframite. It is characterized by the biotite porphyritic monzogranite, biotite-muscovite porphyritic syenogranite, muscovite-zinnwaldite-albite porphyritic granite with topaz and pegmatite facies. Mineral chemistry analyzes reveal the presence of biotite and muscovite in the oldest granite facies and prove the sodium character of plagioclases (albite) and variation in micas composition, from muscovite to predominantly zinnwaldite in the muscovite-zinnwaldite-albite porphyritic granite with topaz facies. These are peraluminous rocks belonging to monzogranitic calcium-alkaline series of high potassium to shoshonitic to sodium alkaline. Magmatism is compatible with A type granite, rapakivi, post-collisional to anorogenic associated with an intraplate environment to a post-collisional magmatic arc environment, with placement in tension structures correlated to the Itapirapuã Shear Zone, in an extensional environment at the end of Ribeira Orogenesis collisional event.
Litogeoquímica E Química Mineral Das Rochas Do Maciço Correas
Keywords: Correas Granite; Geochemistry; Mineral Chemistry